Impact of responsible tourism on destination sustainability and quality of life of community in tourism destinations - Paul V. Mathew and Sreejesh S (Journal of Hospitality and Tourism Management, 2017)
The primary objective of the study is to examine the impact of perceived responsible tourism on perceived quality of life of communities in tourist destinations and to analyze the mediating role of perceived destination sustainability. A questionnaire-based survey conducted to collect responses from a sample of 432 residents from 3 different tourism destinations in India. From the data analysis, it was found that as the residents of the local community, perceived responsible tourism plays a pivotal role in the formulation of perceived destination sustainability, which in turn impacts their perceived quality of life. Thus, the study findings offer implications for the successful management of tourism businesses as well as the community sustainability and their well-being.